Thermal conductivity and viscosity models of metallic oxides nanofluids - Alawi, Omer A.; Sidik, Nor Azwadi Che; Xian, Hong Wei; Kean, Tung Hao; Kazi, Salim Newaz (Elsevier, 2018)
For over ten years, investigators focused on determining and modelling the effective thermal conductivity and viscosity of nanofluids. Lately, many theoretical and experimental investigations on convective heat transfer have been performed on the augmentation of heat transfer by utilizing suspensions of nanometer-sized solid particle materials (metallic or nonmetallic) in base fluids. The main purpose of this work is to determine the thermal conductivity and viscosity of various types of metallic oxides (Al 2 O 3 , CuO, SiO 2 and ZnO) for nanoparticle concentrations of 1–5 vol% at temperatures of 300–320 K and nanoparticle shapes (blades, platelets, cylindrical, bricks, and spherical). The results illustrate that the effective thermal conductivity and thermal conductivity ratio of metallic oxide nanofluids increase with temperature and nanoparticles volume fraction but decreases nanoparticle size intensifies. Besides that, the results of effective viscosity and viscosity ratio obtained indicate a considerable rise with the increase of nanoparticles concentration. Thus, optimum nanoparticle concentration is essential to be determined in forming nanofluids that can enhance thermal systems performance. Finally, it is found that nanoparticles shape has great impact on the thermophysical properties of nanofluids.